An Analytical Study of The Content of The Arabic Textbook for Students at the State Islamic High School by Categories of Analysis by Rushdi Ahmad Taima - Maesaroh, Siti (JURNAL IJ-ATL, 2024)
This study aims to analyze the content of the textbook al-‘Arabiyyah li al-Dārisiin for twelfth-grade students used at Madrasah Aliyah Negeri 1 Lamongan, by examining its conformity based on the content analysis categories developed by Rushdi Ahmad Thu‘aimah. This framework was chosen due to its more comprehensive scope compared to other analytical models. The study employed a qualitative approach using content analysis as its method. Data were collected through observation, interviews, and documentation. The findings reveal that the textbook al-‘Arabiyyah li al-Dārisiin contains a foreword by the author, a vocabulary list, and instructional materials organized into five thematic units. Each unit includes four language skills: listening, speaking, reading, and writing. Overall, the content of this textbook is largely aligned with Rushdi Ahmad Thu‘aimah’s analytical categories, particularly in terms of general data, book layout, and material characteristics. However, several components are lacking, such as the absence of a teacher’s guide, evaluation instruments, and supporting audio recordings.